The silver chair - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperTrophy, 1994)
Two English children undergo hair-raising adventures as they go on a search and rescue mission for the missing Prince Rilian, who is held captive in the underground kingdom of the Emerald Witch.
5.7
5-8
5-8
Kirkus Review
Christian Library Journal starred
840
Keywords: Princes -- Fiction; Witches -- Fiction; Narnia (Imaginary place) -- Fiction; Friendship -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Princes -- Fiction; Witches -- Fiction; Narnia (Imaginary place) -- Fiction; Friendship -- Fiction; Adventure fiction; Fantasy fiction